2017
DOI: 10.1080/10691898.2017.1370363
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Literacy as a Function of Online Versus Hybrid Course Delivery Format for an Introductory Graduate Statistics Course

Abstract: Statistical literacy refers to understanding fundamental statistical concepts. Assessment of statistical literacy can take the forms of tasks that require students to identify, translate, compute, read, and interpret data. In addition, statistical instruction can take many forms encompassing course delivery format such as face-to-face, hybrid, online, video capture, and flipped. In this study, we examined statistical literacy of graduate students using a validated assessment tool (the Comprehensive Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Castaño-Muñoz et al (2014) reported BL can be more effective than face-to-face, but only when interactive learning is also included in the BL course. Other studies (e.g., Hahs-Vaughn et al, 2017; Lim et al, 2019) showed students perform comparably in a BL course and a fully online course.…”
Section: Blended Learning Overviewmentioning
confidence: 90%
“…Castaño-Muñoz et al (2014) reported BL can be more effective than face-to-face, but only when interactive learning is also included in the BL course. Other studies (e.g., Hahs-Vaughn et al, 2017; Lim et al, 2019) showed students perform comparably in a BL course and a fully online course.…”
Section: Blended Learning Overviewmentioning
confidence: 90%
“…10), the words that stand out most frequently within the topics are: teaching, online course design, statistics, R, active learning, online learning, elearning, flipped classroom, online course, and introductory statistics; This indicates that currently the teaching of statistics is taught using virtual platforms designed taking into account the perspectives of the students. A broader evaluation of the topics indicates that experimental research was carried out to verify the effectiveness of the use of virtual tools for teaching statistics [18,25,[36][37][38][39][40].…”
Section: B Clustering and Thematic Analysismentioning
confidence: 99%
“…Many statistics education papers related to online learning focus on predicting student performance (Scherrer, 2011, Hahs-Vaughn et al, 2017, and Gundlach et al, 2015, but do not consider or tie performance to use of course resources. We have found evidence that higher performing students adhered to the intended learning design more consistently and more effectively used course resources throughout the term.…”
Section: Conclusion and Course Changesmentioning
confidence: 99%
“…In the statistics education field, most of the studies in online learning focus on comparing students' performance (measured by final course grades, CAOS and SRA assessments, and other course assignment's grades) across different modes of instruction: online, face-to-face, and hybrid. Mixed results have been reported as some studies find evidence of face-to-face students performing better (Scherrer, 2011) while others finding little to no evidence of a difference in statistical literacy (Hahs-Vaughn et al, 2017), statistical reasoning (Gundlach et al, 2015) knowledge, or final course grades (Shotwell & Apigian 2015) across delivery methods. Other studies focus on how student's attitudes and anxieties towards statistics can predict course outcomes and comparison of student's attitudes across different modes of instructions (Zimmerman & Austin, 2018;Gundlach et al, 2015).…”
Section: Introductionmentioning
confidence: 99%